2007
DOI: 10.1073/pnas.0707155104
|View full text |Cite
|
Sign up to set email alerts
|

Space flight alters bacterial gene expression and virulence and reveals a role for global regulator Hfq

Abstract: A comprehensive analysis of both the molecular genetic and phenotypic responses of any organism to the space flight environment has never been accomplished because of significant technological and logistical hurdles. Moreover, the effects of space flight on microbial pathogenicity and associated infectious disease risks have not been studied. The bacterial pathogen Salmonella typhimurium was grown aboard Space Shuttle mission STS-115 and compared with identical ground control cultures. Global microarray and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
495
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(525 citation statements)
references
References 27 publications
26
495
1
3
Order By: Relevance
“…One of the most exciting results reported from ISS research is the confirmation that common pathogens change and become more virulent during space flight 10 . The Microbe (Effect of Spaceflight on Microbial Gene Expression and Virulence) experiment was performed in September 2006; it examined changes in three microbial pathogens.…”
Section: Biological Sciences In Microgravitymentioning
confidence: 99%
“…One of the most exciting results reported from ISS research is the confirmation that common pathogens change and become more virulent during space flight 10 . The Microbe (Effect of Spaceflight on Microbial Gene Expression and Virulence) experiment was performed in September 2006; it examined changes in three microbial pathogens.…”
Section: Biological Sciences In Microgravitymentioning
confidence: 99%
“…The invasion of S. enterica serovar Typhimurium into the intestinal epithelial cells is the crucial step in pathogenesis. Wilson et al (2007) reported that S. enterica serovar Typhimurium samples grown during the weightlessness of space flight exhibited enhanced virulence in a mouse infection model, along with extracellular matrix accumulation consistent with a biofilm.…”
Section: Biofilm and Virulencementioning
confidence: 99%
“…Indeed, several in-flight studies have reported that the microgravity environment encountered during spaceflight alters bacterial growth and physiology, antibiotic resistance, and virulence. 24,26 In combination with a reduced innate immune system (as witnessed in mouse models during and after spaceflight 27 ), the increased virulence in bacteria presents a significant threat to the health of the crew during long-term space exploration.…”
Section: Biological Model Systems For Space Sciencementioning
confidence: 99%